GROUND PENETRATING RADAR DATA ANALYSIS BY USING MODELLING WITH FINITE DIFFERENCE METHOD: CASE STUDY IN BELAWAN PORT - Siregar, Hans Elmaury Andreas (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2016)
Ground Penetrating Radar (GPR) is one of non destructive geophysics methods which is appropriate used to identify subsurface object with depth penetration less than 70 meter. High data resolution as well as relatively unprolonged and manageable data acquisition make this method becoming convenient supporting method to increase near surface data for other geophysics methods. The depth penetration of GPR varies with the frequency of antenna. Getting optimum depth penetration before field acquisition data some numerical simulation should be accomplished in order to perceive antenna frequency and processing technique that used, so the depth of target zone can be achieved. The Finite Difference (FD) is one one of numerical anaysis technique that mostly used to determine differential equation. By using FD method, the solution of electromagnetic waves equation can be obtained and the image of numerical simulation can be displayed. In line with this radar image from numerical simulation, the relationship of frequency and depth penetration on the media used is acquired. Media used in this simulation are sand, clay, sandy clay, clayey sand and concrete. Through numerical simulation from this research, we conclude that GPR method able to distinguish boundary layer among each medium. Processing technique is accomplished to comprehend suitable processing stages for high resolution radar image that can be interpreted. Data acquisition and processing technique from simulation have been implemented in field experiment and very helpful to apprehend GPR characteristic signal in subsurface map in Belawan port.